Effrctivenes Of The Biology Learning During The Covid-19 Pandemic Class X MIPA Mas Al Wasliyah Merbau North Labuhanbatu Regency - Hendrika Saputra; Padilah; Ade Irwansyah Putra Nasution (CV. AFDIFAL MAJU BERKAH, 2021)
This study aims to determine the supporting and inhibiting factors as well as the effectiveness of learning biology during the covid-19 pandemic at MAS Al Wasliyah Marbau. This research is a qualitative descriptive type with data collection techniques through interviews, questionnaires, observation and documentation. Data analysis used in the form of data collection, data reduction, and data presentation. The results of this study indicate that the inhibiting factors for learning from home in biology are internet networks, student absence from online learning, economic conditions of students, and possession of gadgets or laptops. The supporting factors are technology, learning places in accordance with the COVID-19 health protocol, adequate learning resources and learning media, online learning implementation plans designed by teachers, students' enthusiastic attitude in studying, and adequate infrastructure. In conclusion, 82% of biology learning at MAS Al Wasliyah Marbau runs effectively in accordance with government regulations through Circular Letter No. 15 of 2020.